Malaysia : Court Backlog and Delay Reduction Program, A Progress Report - World Bank (Washington, DC, 2014)
This study reviews the initial results of efforts by the Federal Court of Malaysia to improve judicial performance, especially in the areas of backlog and delay reduction. It was written at the request of the Court and was intended to evaluate progress to date, suggest how the program might be improved, and provide recommendations on further actions in a second phase reform. The work is based on documents and statistics made available by the Court, two weeks of fieldwork (January 2011) in Putrajaya (the Federal Government Administrative Center and seat of the Federal Court and Court of Appeal) and the High Courts in the two largest court complexes, Kuala Lumpur and Shah Alam, and a follow-up visit in May 2011 to discuss the preliminary conclusions with the Judiciary and also to update material on this rapidly moving program. While intended as an external review of the Malaysian Judiciary's recent reform efforts, the study describes a model and lessons applicable to court systems elsewhere that are facing similar problems or wishing to improve other aspects of their performance.